Phenotypic and genotypic characterisation of Burkholderia cenocepacia J2315 mutants affected in homoserine lactone and diffusible signal factor-based quorum sensing systems suggests interplay between both types of systems. - Claudia Udine (PLoS ONE, 2013)
Many putative virulence factors of Burkholderia cenocepacia are controlled by various quorum sensing (QS) circuits. These QS systems either use N-acyl homoserine lactones (AHL) or cis-2-dodecenoic acid ("Burkholderia diffusible signal factor", BDSF) as signalling molecules. Previous work suggested that there is little cross-talk between both types of systems. We constructed mutants in B. cenocepacia strain J2315, in which genes encoding CepI (BCAM1870), CciI (BCAM0239a) and the BDSF synthase (BCAM0581) were inactivated, and also constructed double (ΔcepIΔBCAM0581, ΔcciIΔBCAM0581 and ΔcepIΔcciI) mutants and a triple (ΔcepIΔcciIΔBCAM0581) mutant. Subsequently we investigated phenotypic properties (antibiotic susceptibility, biofilm formation, production of AHL and BDSF, protease activity and virulence in Caenorhabditis elegans) and measured gene expression in these mutants, and this in the presence and absence of added BDSF, AHL or both. The triple mutant was significantly more affected in biofilm formation, antimicrobial susceptibility, virulence in C. elegans, and protease production than either the single or double mutants. The ΔBCAM0581 mutant and the ΔcepIΔBCAM0581 and ΔcciIΔBCAM0581 double mutants produced significantly less AHL compared to the WT strain and the ΔcepI and ΔcciI single mutant, respectively. The expression of cepI and cciI in ΔBCAM0581, was approximately 3-fold and 7-fold (p<0.05) lower than in the WT, respectively. The observed differences in AHL production, expression of cepI and cciI and QS-controlled phenotypes in the ΔBCAM0581 mutant could (at least partially) be restored by addition of BDSF. Our data suggest that, in B. cenocepacia J2315, AHL and BDSF-based QS systems co-regulate the same set of genes, regulate different sets of genes that are involved in the same phenotypes and/or that the BDSF system controls the AHL-based QS system. As the expression of the gene encoding the C6-HSL synthase CciI (and to a lesser extent the C8-HSL synthase CepI) is partially controlled by BDSF, it seems likely that the BDSF QS systems controls AHL production through this system.